Ubóstwo w społeczeństwie dobrobytu? O partnerskie zaangażowanie Kościołów oraz instytucji europejskich w walkę z ubóstwem w Unii Europejskiej - MARX, Reinhard; MIKULSKA, Patrycja (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
The article takes as its point of departure the actual poverty present in welfare societies of the European Union. Having described and evaluated the efforts made in the field of overcoming poverty by the European institutions, especially within the framework of the European Year for Combating Poverty and Social Exclusion, the article points to deficits in the measures adopted against poverty and exclusion, and to the definite areas where action should be taken. Combating poverty is seen as one of the urgent tasks that must be undertaken in the coming years. Social justice must be included among the main goals of national and European policies. For Christians, special concern for the poor is a noble task. From its beginnings, the social doctrine of the Catholic Church has expressed an increasingly clear stand towards those issues, as it is manifested also in the Encyclical Caritas in veritate of Pope Benedict XVI, and is currently making an important contribution to overcoming poverty and exclusion. Translated by Patrycja Mikulska